Composition, anti-LDL oxidation, and non-enzymatic glycosylation inhibitory activities of the flavonoids from Mesembryanthemum crystallinum - Sun, Meiling; Wei, Ying; Feng, Xiaoguang; Fan, Junfeng; Chen, Xiangning (Frontiers in Nutrition, 2022)
This study identified the constituents of purified flavonoids isolated from Mesembryanthemum crystallinum (PEF) and examined their inhibitory effects on low-density lipoprotein (LDL) oxidation and non-enzymatic glycosylation. More than 30 kinds of flavonoid compounds were identified in M. crystallinum, including tangeretin, nobiletin, farrerol, protocatechualdehyde, diosmin, and rutin. Moreover, tangeretin accounted for about 50.85% of all the flavonoids. PEF had a low IC50 value for 1,1-diphenyl-2-picrylhydrazyl radicals (DPPH·), hydroxyl radical (·OH) and superoxide anion free radical (O-2·) scavenging. They were found to effectively delay and inhibit the production of conjugated diene (CD) and thiobarbituric acid reactive substance (TBARS) during LDL oxidation. Meanwhile, scanning electron microscopy (SEM) of the LDL oxidation incubation system with PEF showed a smooth and dense surface, with no obvious cavitation phenomenon. Furthermore, PEF effectively inhibited the production of LDL glycosylation products and showed a strong inhibitory effect on the latter stage. The electrophoresis of advanced glycosylation end products (AGEs) further confirmed that PEF can effectively prevent the cross-linking between glucose and proteins, protecting LDL from glycosylation-induced damage.